Effective Ayurvedic Treatment of Pilonidal Sinus using Udumber Ksheer Sutra: A Case Study - Harshadkumar Prajapati; Ashvini D. Pardhekar; Abhilash Pardhekar; Manisha Davkare (Journal of Pharmacy and Bioallied Sciences)
Pilonidal sinus, also known as “jeep bottom,” is common among people who sit a lot, such as cab drivers. It mostly affects men and young adults and is associated with thick hair. Surgical techniques are available for treatment, but the condition has a relatively high recurrence rate. The Kshara Sutra method described in the Sushruta Samhita offers a minimally invasive treatment option. Pilonidal disease is estimated to affect about 26 out of every 100,000 persons, with around 0.7% of people affected. This study focuses on the diagnosis and treatment of patients who have Naadi Vrana (Pilonidal Sinus) using Udumber Ksheer Sutra. The Kshara Sutra is a minimally invasive, cost-effective technique with a low recurrence rate for treating pilonidal sinus. Udumber Ksheer Sutra management has also proven to be beneficial as a curative therapy for the pilonidal sinus.